Design, Analysis and Fabrication of Plastic Injection Mould for Tensile Test Specimen - Mohd Ariffin, Mohd Khairol Anuar (2001)
The a i m of this project is to design, analyse and produce the plastic injection mould for tensile test specimen. It is also concerned with presenting the technique, method, and theory for producing the plastic injection mould. This project is divided into three sections, namely design, analysis and fabrication. Each of the previous mentioned section is illustrated in proper order to ensure that the readers have a good understanding on how the process is done. The design of the mould is governed first by its intended function and is restricted by the specification limitation of the injection moulding process. Two other factors have to be considered such as material specification and mould condition. The total design method was used in this project to design, analyse and fabricate the mould. This concept allows us to produce the best conceptual design. The techniques in Total Design Method used were Product Design Specification, Quality Function Deployment and Matrix Evaluation System. In the design section, Unigraphics CAD/CAM system is used to produce the detail design and the numerical control codes that are needed to assist machining mould components. Careful consideration has to be taken during selection of various machines that can be used to manufacture the mould. In this project a Computer Numerical Control (CNC), milling, drilling, grinding and Electrode Discharge Machining (EDM) machines were used to machine the mould components. The rework cost is a major problem to the mould making industries, therefore by integrating the Moldflow analysis software (part advisor version 4) into the mould fabrication process this problem can be avoided. This software simulates how the molten plastic enters the mould during the injection process and also the possible defects that might occur. This step will eliminate the rework cost and time as all the possible errors are eliminated before it actually occur in the actual production process. The quality of the mould and injected product depend on the processing conditions such as melt temperature, mould temperature and injection pressure as we" as the machines used to fabricate the mould. As a conclusion the aim of the project to create a mould for tensile test specimen has been achieved.